Spectral and temporal properties of BeXRB pulsars during super-Eddington outbursts - Vasilopoulos, G.; Haberl, F.; Koliopanos, F. (2017)
Nearby galaxies are well suited for investigating X-ray source populations in environments different to our own Galaxy. Sources in these galaxies have well determined distances and are less absorbed than sources in the Galactic plane. The Large and the Small Magellanic Clouds (MC) are the nearest gas-rich star-forming galaxies and their gravitational interactions are believed to have tidally triggered recent bursts of star formation. Here, we will focus on the X-ray spectral and temporal properties of three Be/X-ray binary pulsars located in the MC that have been observed in the recent years with XMM-Newton during super-Eddington outbursts. Phase-resolved spectral analysis has revealed the presence of a non-pulsating soft component. By analysing multiple observations, corresponding to different luminosity levels, we argue that this component could not originate from the surface of a traditional thin disk, but most probably this emission is a result of reprocessed emission from material located near the NS magnetospheric radius. Interestingly, we find that the temperature of this component does not change much with the luminosity of the system, in contrast to its size that increases with increasing luminosity. We argue that this indicates the formation and expansion of an envelope around the magnetosphere of the NS.